Tradução de normas e políticas internacionais: a localização da Agenda 2030 por meio de uma abordagem situada - Norcia, Raffaela Valdemarca (2021)
The research seeks to present a situated approach to the process of diffusion and translation of international norms and understand how it allows a critical view of the interrelationship between international norms and public policies, through the case of localizing the 2030 Agenda, based on the Sustainable Development Goals (SDG). Diving into the case demonstrates the importance of the process of translating the agenda in a way that is situated in its context and also seeks to bring two distant kinds of literature closer together, Public Policies and International Relations, offering a holistic analysis of localization and creating a nexus between the theoretical effort and the possibilities of applying the theory